Package and board level reliability modeling of advanced CSP pakages for telecommunication applications - Tee, Tong Yan (2008)
Market for telecommunication products (e.g., mobile phones) is very competitive, demanding products which are more reliable, higher performance, lighter, smaller, cheaper, and shorter time-to-market. These technology requirements are possible with the recent development of advanced Chip Scale Packages (CSPs), such as thin-profile fine-pitch Ball Grid Array (TFBGA), Quad-Flat-No-lead (QFN), and wafer-level CSP (WL-CSP). However, due to limited product development time, these CSPs are usually not tested and studied in detail before introduction to the market. As a result, the package design may not be optimized for various reliability requirements, e.g., popcorn, thermal cycling test, and drop test.